WHAT IS COMPANY IMAGE AS A MODERATION VARIABLE FOR CUSTOMER SATISFACTION IN THE EXPEDITION BUSINESS? - Humairoh, Humairoh; Annas, Mohammad (Dynamic Management Journal, 2024)
The aim of this research is to analyze the influence of service quality with company image as a moderating variable on customer satisfaction in the expedition business. The sample used was 96 people using a simple random sampling technique among Ninja Xpress expedition users using a survey method by distributing questionnaires. The collected data was analyzed using SmartPLS. The research results show that service quality has a positive and significant influence on customer satisfaction, service quality has a positive and significant influence on company image, company image has a positive but not significant influence on customer satisfaction and company image is not a moderating variable between service quality and customer satisfaction.